Technological Advancements and Strategic Roles of Fourth-Party Logistics (4PL): A Systematic Literature Review - Rizki Aditya Wardhana; Bambang Darmawan; Aulia Zikri Rahman (JTI: Jurnal Teknik Industri, 2025)
Fourth-Party Logistics (4PL) has emerged as a critical strategic model for managing complex supply chains in the digital era. This systematic literature review analyzed 38 peer-reviewed articles (2020-2025) from the Scopus database to examine technological advancements and strategic roles of 4PL in supply chain management. Three research questions guided the analysis: optimization technologies supporting 4PL operations, strategic mechanisms improving supply chain outcomes, and cost reduction strategies enabling 4PL adoption. Findings demonstrate that advanced optimization technologies including Conditional Value-at-Risk (CVaR), stochastic programming, and reinforcement learning effectively manage transportation uncertainty and enhance operational efficiency. Strategic mechanisms such as coordinated ICT infrastructure, sophisticated matching models, and innovative financing arrangements significantly improve service quality and customer satisfaction. Cost reduction and sustainability strategies, including flexible resource management, warehouse optimization, and blockchain implementation, enable organizations to achieve cost reductions up to 38% while maintaining environmental compliance. However, implementation barriers in regulatory compliance, human resource management, and digital infrastructure remain significant challenges. The research concludes that 4PL adoption requires integrated approaches balancing technological innovation with organizational capability development. Future research should prioritize context-specific implementation frameworks for emerging markets, particularly in developing economies such as Indonesia, to address unique supply chain challenges while supporting economic growth and operational resilience. Keywords: Customer Satisfaction, Fourth-Party Logistics, Outsourcing Strategy, Supply Chain Management